Profile of Student Fear Public Speaking Based On Emotional Maturity and Self Efficacy - Utomo, Hanggara Budi (JOURNAL OF EDUCATION SCIENCE, 2015)
Fear of public speaking is influenced by several factors, including the factor of emotional maturity and self efficacy factor. This study aims to investigate the relationship between emotional maturity and self efficacy with public speaking anxiety in students. This research was conducted at the University of Nusantara PGRI Kediri and by quantitative (correlational) research. Sample is student counseling about 132 people. The sampling technique used is random sampling. The type of instrument used in this study of Emotional Maturity scale, scale Self Efficacy and Anxiety scale public speaking using a Likert scaling models. The results showed there was no correlation between the emotional maturity in front of public speaking (rxy = -0,094); there is a relationship between Self Efficacy with Fear of public speaking ((rxy = -0,224); and there is a relationship between Emotional Maturity and Self Efficacy with Fear of public speaking (R Â = 0,043).